An Experimental Study of the Dynamic Split Tension Properties of Reinforced Concrete - Zhao, Z.; Jing, L.; Pei, Q.; Ma, H.W.; Wang, Z.H. (Проблемы прочности, 2016)
Dynamic split tensile tests of reinforced concrete were carried out using the split Hopkinson pressure bar experimental technique to determine the failure modes of reinforced concrete at different strain rates, and the effect of reinforcement ratio and reinforcement layouts on the dynamic performance. The specimens with nine reinforcement ratios were used in the tests. Experimental results show that the tensile strength of reinforced concrete exhibits a critical strain rate, beyond which larger increases in dynamic strength of specimens occur. The dynamic split tension strength of reinforced concrete is demonstrated to be greater than the plain concrete with the same strength grade over the range of tested strain rate. The results also indicate that the dynamic split tension strength of specimens enhances with the increase of reinforcement ratio. These findings are instrumental to guide the structural design of reinforced concrete in engineering constructions.